Analisis Pertanggungjawaban Perekam Film Mnggunakan Kamera Video Dalam Bioskop Yang Diunggah Pada Media Sosial - Cahyani Wayuningtias Posangi; Mutia Cherawaty Thalib; Mohammad Taufiq Zulfikar Sarson (Lembaga Pengembangan Kinerja Dosen, 2024)
This research is intended to find out (1) whether recording a film using a video camera and uploading it via Instagram story in the cinema constitutes a copyright violation. (2) what are the legal consequences of violations of film recording using a video camera in a cinema that is uploaded and distributed on social media Instagram stories? This research uses a type of normative legal research with a statutory approach, conceptual approach and case approach. The sources of legal materials used are primary legal materials and secondary legal materials. The primary legal materials in this research are legal materials of an authoritative nature such as statutory regulations, court decisions, and treatises, as well as official state documents. Meanwhile, secondary legal materials consist of books, scientific articles and other sources that are considered relevant to the research to be conducted. The results of the research show, firstly, that the act of recording film scenes by members of the public in a cinema, which in turn is uploaded to social media, cannot necessarily be classified as a criminal offence, on the grounds that the elements of this criminal act cannot be fulfilled. On the other hand, the community's intention to violate economic rights for commercial purposes must be fulfilled first to determine the action as a criminal offense. Second, legal protection by the government, in this case the Directorate General of Intellectual Property at the Ministry of Law and Human Rights of the Republic of Indonesia for creators or rights holders, can be done in two ways: the first is by instilling a sense of awareness in the community, and the second is by creating a legal protection policy ( new legal protection policy) by revising the Law on Copyright.